2013
DOI: 10.1175/bams-d-11-00176.1
|View full text |Cite
|
Sign up to set email alerts
|

Toward Global Drought Early Warning Capability: Expanding International Cooperation for the Development of a Framework for Monitoring and Forecasting

Abstract: Drought is a global problem that has far-reaching impacts, especially on vulnerable populations in developing regions. This paper highlights the need for a Global Drought Early Warning System (GDEWS), the elements that constitute its underlying framework (GDEWF), and the recent progress made toward its development. Many countries lack drought monitoring systems, as well as the capacity to respond via appropriate political, institutional, and technological frameworks, and these have inhibited the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
112
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 168 publications
(114 citation statements)
references
References 23 publications
(1 reference statement)
1
112
0
1
Order By: Relevance
“…Therefore, monitoring and forecasting of agricultural and hydrological droughts not only provide more relevant guidelines for the management of agricultural and water resources but also raise challenging scien-5478 X. Yuan et al: Understanding and seasonal forecasting of hydrological drought tific questions on the mechanism and predictability of multiscale drought processes (Pozzi et al, 2013;Wood et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, monitoring and forecasting of agricultural and hydrological droughts not only provide more relevant guidelines for the management of agricultural and water resources but also raise challenging scien-5478 X. Yuan et al: Understanding and seasonal forecasting of hydrological drought tific questions on the mechanism and predictability of multiscale drought processes (Pozzi et al, 2013;Wood et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A drought early warning system with seasonal predictions of drought onset, severity, persistence, and spatial extent in a timely manner would provide invaluable information to decision-makers and stakeholders. There are a number of research and operational drought (or hydrologic) prediction systems (Pozzi et al, 2013;Mishra and Singh, 2010;AghaKouchak and Nakhjiri, 2012), including the Climate Prediction Center Seasonal Drought Outlook (Steinemann, 2006), the University of Washington's Surface Water Monitor (Wood and Lettenmaier, 2006;, Princeton University's drought forecast system (Luo and Wood, 2007;Li et al, 2008;, USMexico Drought Prediction Tool , and the Global Integrated Drought Monitoring and Prediction System (GIDMaPS; . Despite all these efforts, a community white paper by the World Climate Research Program identified sub-seasonal to seasonal drought prediction as one of the major research gaps in hydroclimatology (WCRP, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…E. • global precipitation Pozzi et al, 2013;Serrat-Capdevila et al, 2013;Lettenmaier et al, 2015). However, P is also one of the meteorological variables that is most difficult to estimate, due to its high spatiotemporal heterogeneity (Daly et al, 1994;Herold et al, 2015).…”
mentioning
confidence: 99%